Optimalisasi Peran Kader Sebaya untuk Pencegahan Stunting Sejak Dini Pada Remaja Putri - Budhi, Ni Gusti Made Ayu Agung; Aticeh, Aticeh; Follona, Willa (Jurnal Pengabdian kepada Masyarakat (ABDIKEMAS), 2025)
Stunting is a chronic health issue that significantly impacts the quality of human resources in the future. Adolescent girls, as future mothers, play a crucial role in the early prevention of stunting, particularly through education on anemia and the postponement of early marriage. This community engagement program aimed to empower adolescent health cadres (Posyandu Remaja) as peer educators through a series of activities including knowledge refreshment, anemia screening, health education, and mentoring. The program targeted 10 cadres and 16 adolescent girls in Pulogadung Subdistrict, East Jakarta. The results showed a notable improvement in cadre knowledge (pretest score increased from 40 to 75), identification of mild anemia cases in 25% of adolescent girls, and enhanced capacity of cadres in delivering health education. These findings demonstrate that the peer group approach is effective in improving health literacy and promoting early stunting prevention among adolescents. This outcome is essential to support sustainable adolescent health improvement programs within the community.